Multidirectional evaluations of a carbon air filter to verify their lifespan and various performances. (December 2018) - Lim, Tae Hwan; Yeo, Sang Young; Lee, So Hee
Abstract: Carbon air filter, called cabin filter, has been used to remove harmful airborne particles and gases causing human disease. This filter is composed of nonwoven and meltblown layers with activated carbons and is widely employed for such purposes as automobile air conditioning. Here, a fiber binder adapted cabin filter was prepared to simplify the fabrication process, enhance the economic benefits, and improve the filtration and gas adsorption efficiencies of the cabin filter. It exhibited higher filtration and gas adsorption efficiencies than a conventional liquid binder adapted cabin filter. Furthermore, multidirectional evaluations of the filtration efficiencies were performed considering various aerosol types, various particle sizes, inclusion or exclusion of electrostatics, various gas adsorptions of the filter unit, and lifespan expectation through dust feeding. A quality factor was introduced to substantiate the filter performance by considering the correlation between pressure drop and particle penetration. The optimal weight of the meltblown layer was first selected as 20 g/m 2, and it was confirmed that the mechanical and filtration properties of the fiber binder-adapted cabin filter were higher than those of a conventional cabin filter. An electro-charging effect was tested to demonstrate that it filled the efficiency vacancy under 1 µm and enhanced the filtration efficiency of the fiber binder adapted cabin filter compared with that of the uncharged cabin filter. Finally, the filter has a longer lifespan than the conventional one because it has more space to store dust. Overall, our research demonstrates a method to fabricate a fiber binder-adapted cabin filter and evaluates its performance via comprehensive evaluations. Highlights: We perform the multidirectional evaluations of air filter performance. We analyze synthetically the filter performance with various testing standards. Efficiency enhanced cabin air filter is prepared by our novel technique. The filter is considered not only efficiency but the processability and cost-effect. The method of lifespan expectation of cabin filter is suggested by laboratory scale test.